How do Innovation and Entrepreneurial Orientation affect Competitive Advantage through Product Quality of Culinary Sector MSMEs? - Eva Yuniarti Utami; Rina Destiana; Rawi Rawi; Tri Neliana; Muhlis Muhlis (Universitas Negeri Makassar, 2023)
This study aims to analyze the influence of innovation and entrepreneurial orientation on competitive advantage through product quality in Micro, Small and Medium Enterprises (MSMEs) in the culinary sector in Makassar City. Data was collected from culinary MSMEs through questionnaire distribution surveys, and then analyzed using statistical methods. The research population is culinary MSMEs in the city of Makassar which amounts to 1500 MSMEs. While the sampling technique uses the Proportional Random Sampling technique, which is calculated using from Slovin with a sample result of 102 respondents or 22% of the population. These results show the importance of innovation, entrepreneurial orientation, and focus on improving product quality as a strategy to increase the competitive advantage of culinary MSMEs in Makassar City. The practical implication of this research is the importance of culinary MSMEs to continue to encourage innovation and entrepreneurial orientation and improve the quality of their products to win the competition in a competitive market.